The effect of using method timer media on reducing eye fatigue industry workers - Santi, Ratna Estika; Muryani, Sri; Kasjono, Heru Subaris (International Journal of Public Health Science (IJPHS), 2024)
The outcomes of an initial research on eye fatigue in the Digital Industry in Yogyakarta, Indonesia revealed that 76% of the employees encountered complaints of eye fatigue as a result of prolonged computer usage. Eye fatigue is considered one of the parameters of office ergonomics in accordance with Indonesian Minister of Health Regulation No. 48 of 2016. One method recommended by this regulation to mitigate eye fatigue is to incorporate short breaks using the 20-20-20 technique. However, a considerable number of workers tend to disregard these recommendations, necessitating the use of media reminders, such as timers, to enforce discipline among workers. The objective of this research was to assess the impact of employing a timer-based media using the 20-20-20 method on the reduction of eye fatigue. The research employed a quasi-experimental design with a nonequivalent control group. In this research, a total of forty workers were selected as the sample population and subsequently divided into two groups: the intervention group and the control group. Sampling was conducted to select a total of 20 workers for each group through purposive sampling. Bivariate analysis was performed using the Sign test and Mann-Whitney test, with a significance threshold of 95% (α=0.05). The results of the statistical tests conducted in both the intervention and control groups revealed a significant difference in reducing eye fatigue, with a p-value of 0.041. This research concludes that the utilization of the 20-20-20 method timer media has a significant effect on reducing eye fatigue among workers.